Investigating the Economic Burden and Social Support in Individuals With Post-traumatic Stress Disorder: A Scoping Review - Amos Nnaemeka Amedu; Veronica Dwarika (Gonabad University of Medical Sciences, 2024)
Background: Post-traumatic stress disorder (PTSD) is a well-known psychiatric disorder that can occur after a major traumatic event and adversely impact the individual's mental health. PTSD is a multifaceted mental health problem that requires long periods of treatment and expensive treatment protocols. Despite significant advances in treatment, there is little evidence of the economic burden and social support associated with PTSD. Hence, this study examines empirical research on the economic burden and social support associated with patients with PTSD. Methods: In this study, we used the preferred reporting items for systematic reviews and meta-analyses guided scoping review protocol to assess the research on the economic burdens and social support associated with PTSD patients. Accordingly, we selected 14 primary research studies examining the economic burden and 17 primary studies examining social support for PTSD patients.  Results: PTSD patients incur a high economic burden worldwide with huge direct cost variability. Meanwhile, social support is an impactful approach to curbing the impacts of PTSD on patients. This study demonstrated the substantial role of social support in reducing PTSD symptoms and as a significant moderator in the treatment of PTSD patients. Conclusion: PTSD is a mental health problem associated with a highly variable economic burden on patients and healthcare systems across the globe. In addition, social support facilitates the speedy recovery of PTSD patients. Because of the high economic burden associated with PTSD, the World Health Organization (WHO) should formulate a policy that improves resource allocation specifically for vulnerable individuals with PTSD.